2019
DOI: 10.1038/s41524-019-0246-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order topological solitonic insulators

Abstract: Pursuing topological phase and matter in a variety of systems is one central issue in current physical sciences and engineering. Motivated by the recent experimental observation of corner states in acoustic and photonic structures, we theoretically study the dipolar-coupled gyration motion of magnetic solitons on the twodimensional breathing kagome lattice. We calculate the phase diagram and predict both the Tamm-Shockley edge modes and the second-order corner states when the ratio between alternate lattice co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 70 publications
1
44
0
2
Order By: Relevance
“…When the surface states of a 3DFOTI are gapped, the intersection of two surfaces of different topological classes, i.e., a hinge, has topologically nontrivial chiral hinge states, leading to a so-called 3D second-order topological insulator (3DSOTI). The well-accepted paradigm is that a d-dimensional material can be a (d − n)th-order topological insulator with 1 n d so that all states in submanifolds, whose dimensions are greater than (d − n + 1), are gapped whereas states are gapless on, at least, one submanifold of dimension (d − n) [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…When the surface states of a 3DFOTI are gapped, the intersection of two surfaces of different topological classes, i.e., a hinge, has topologically nontrivial chiral hinge states, leading to a so-called 3D second-order topological insulator (3DSOTI). The well-accepted paradigm is that a d-dimensional material can be a (d − n)th-order topological insulator with 1 n d so that all states in submanifolds, whose dimensions are greater than (d − n + 1), are gapped whereas states are gapless on, at least, one submanifold of dimension (d − n) [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the spring constant K can be obtained from the relation K = ω 0 |G|, with ω 0 the gyrotropic frequency of a single vortex. For Permalloy (Py) [64,65] nanodisk of vortex state with thickness w = 10 nm and radius r = 50 nm, the gyrotropic frequency ω 0 = 2π × 0.939 GHz, gyroscopic constant G = −3.0725 × 10 −13 J s rad −1 m −2 (Q = 1/2) [53], we have K = 1.8128 × 10 −3 J m −2 . Secondly, the analytical expressions of I and I ⊥ on the distance d between vortices have been obtained in a simplified two-nanodisk system [53].…”
Section: Model and Methodsmentioning
confidence: 99%
“…With extracted patterns from unsupervised learning algorithms, follow-up experiment designs can be conducted for deeper investigation of the system under study.As an example, we show how manifold learning on a simulated 4D-STEM dataset for single-layer graphene automatically reveals real-space neighbor effects on electron deflection patterns recorded on the pixelated detector, that relate to both individual atomic sites and sublattice structures. Additional examples and detailed study on experimental datasets can be found in [7]. In layman's terms, for straightforward visualization purpose, manifold learning will project the whole diffraction patterns into a 2D space based on pair-wise similarity, with a one-to-one mapping between the points in the 2D manifold plane and the diffraction patterns.…”
mentioning
confidence: 99%
“…Much information in 4D-STEM is currently unexploited. To address this fundamental issue, recently developed unsupervised learning algorithms based on graph-analytics and manifold learning [6,7] will allow subtle details, such local symmetry or defects, to be automatically identified, without any prior bias regarding the material structure and instrumental modality. With extracted patterns from unsupervised learning algorithms, follow-up experiment designs can be conducted for deeper investigation of the system under study.…”
mentioning
confidence: 99%